2022
DOI: 10.2807/1560-7917.es.2022.27.42.2200757
|View full text |Cite
|
Sign up to set email alerts
|

High monkeypox vaccine acceptance among male users of smartphone-based online gay-dating apps in Europe, 30 July to 12 August 2022

Abstract: We assess monkeypox vaccination acceptance among male adults in the European Region. We conducted an online survey through two dating apps targeting men who have sex with men, from 30 July to 12 August 2022. We developed Bayesian hierarchical logistic regression models to investigate monkeypox vaccination acceptance. Overall crude vaccination acceptance was 82% and higher in north-western compared to south-eastern European regions. Acceptance strongly rose with perception of increased disease severity and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 16 publications
2
27
1
Order By: Relevance
“…Another Dutch survey recruiting early July 2022 had observed 70% PPV willingness ( 21 ), which was confirmed in the current study showing 73% in the early recruitment at the end of July ( Supplementary material 3 ). A large-scale European survey recruiting in the first half of August, observed 85–90% (northern countries) and 83–88% (western countries) ( 12 ), in line with our current Dutch study showing 86% PPV willingness in the first half of August. It should be noted that willingness fluctuated without showing an independent time trend.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another Dutch survey recruiting early July 2022 had observed 70% PPV willingness ( 21 ), which was confirmed in the current study showing 73% in the early recruitment at the end of July ( Supplementary material 3 ). A large-scale European survey recruiting in the first half of August, observed 85–90% (northern countries) and 83–88% (western countries) ( 12 ), in line with our current Dutch study showing 86% PPV willingness in the first half of August. It should be noted that willingness fluctuated without showing an independent time trend.…”
Section: Discussionsupporting
confidence: 90%
“…People's willingness to accept PPV is a vital step. An online survey in the European region conducted during the peak of the outbreak, in 32,902 users of gay dating apps, demonstrated high willingness to accept PPV in Northern [84.8–90.4%] and Western Europe [83.1–87.7%] and somewhat lower in South-Eastern [60.9–70.2%] and Eastern Europe [59.9–71.1%] ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date among 2SGBTM have demonstrated high overall acceptability of the Mpox vaccine, which may be patterned along social gradients. [6] , [7] , [8] However, acceptability may not predict actual uptake of vaccine and to our knowledge few studies of Mpox vaccine uptake among 2SGBTM have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A survey used a smartphone‐based gay‐dating app to ask about vaccine acceptance using a five‐point rating scale. Of 244 UK men, 89.8% said that they will or probably will get vaccinated for mpox 9 …”
Section: Vaccinationmentioning
confidence: 99%
“…Of 244 UK men, 89.8% said that they will or probably will get vaccinated for mpox. 9 Professor Phillips notes, however, that the vaccine's efficacy isn't clear. "We're still dealing with the outbreak," he says.…”
Section: Vaccinationmentioning
confidence: 99%